Homemaking activities of girls enrolled in two secondary schools in Vigan, Ilocos Sur - Navarrete, Catalina Rosal 1934- (1961)
This study aims to find out the homemaking activities of students enrolled in one private and one public secondary school in Vigan, Ilocos Sur as a basis for curriculum revision. It further attempts to find out if there are differences in the homemaking activities of these two groups of respondents. In the light of these differences, if there are any, is the centralized system justifiable? The results of this study are presented in tables and discussed in manuscript. It was found out that there are differences between the two groups of respondents with regard to their homemaking activities. The respondents in the public school excelled the respondents in the private school in twenty-six types of homemaking activities which are strenuous and those in the latter school excelled those in the former school in only seven types of activities which are light in nature. The socio-economic status of the families appear to e the potent factor that affects the differences in the homemaking activities of these two groups of respondents. It was found out that the respondents in the private school belong to a higher socio-economic status than the respondents in the public school. Some of the practices indicating problems relative to homemaking were also revealed. Some of these practices are eating the "dulang". eating with fingers, bathing outside the bathroom, using the open drainage, and improper sewage disposal. It is therefore suggested that the teachers of these schools concerned should encourage health and sanitation through eating on the table, using silver or coconut spoons, and recommending the construction of native bathroom and sanitary pit, and using the blind drainage. Since this study proves that students from two schools in the same region differ in types and number of homemaking activities, the centralized system of education is not recommended. It is suggested that a national survey should be made to find out if there are differences in the homemaking activities of students in different regions and should there be differences, each region should have a course study adapted to the needs of that particular region. It is hoped that the results of this study will be of great value to the home economics teachers in Vigan, Ilocos Sur in providing them with background information and materials for their use and to administrators to conduct similar studies in different regions in the Philippines as a basis for curriculum construction.